«The irrational is the other»: The mechanisms of interpretation in Anthropology - Ricard Lanata, Xavier (2005)
This article examines two dialogues between the anthropologist and alpaca shepherds of the Ausangate mountains (Cusco region, province of Canchis). Parting from the description and analysis of the concrete interpretation mechanisms used in the anthropological discipline (establishment of a lexicon, logical inferences, etc.), and of its consequences (in particular, the attribution of a pre-rational or irrational mentality, on behalf of the anthropologist, to his farmer-indigent interpreters), the article proposes reflection on the methodological obstacles for an adequate anthropological interpretation of the other cultures. It attempts in this way, to contribute to define, from the hermeneutic practice of anthropology, methodological protection that guarantee the constitution of real spaces of intercultural dialogue.